The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 IEEE International Joint Conference on Biometrics (IJCB) 2017
DOI: 10.1109/btas.2017.8272764
|View full text |Cite
|
Sign up to set email alerts
|

SSERBC 2017: Sclera segmentation and eye recognition benchmarking competition

Abstract: This paper summarises the results of the Sclera Segmentation and Eye Recognition Benchmarking Competition (SSERBC 2017). It was organised in the context of the International Joint Conference on Biometrics (IJCB 2017). The aim of this competition was to record the recent developments in sclera segmentation and eye recognition in the visible spectrum (using iris, sclera and peri-ocular, and their fusion), and also to gain the attention of researchers on this subject. In this regard, we have used the Multi-Angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…To assess changes in the quality of the image by using the biometric authentication system with iris functional visible and IR ranges scanning use Theorem multiplying the probabilities for independent events [6] according to formula (7): P (AB) = P (A) • P (B),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess changes in the quality of the image by using the biometric authentication system with iris functional visible and IR ranges scanning use Theorem multiplying the probabilities for independent events [6] according to formula (7): P (AB) = P (A) • P (B),…”
Section: Resultsmentioning
confidence: 99%
“…It should not be missed that in addition to lighting, you need to take into account the colour of the eyes of the person passing authentication. For example, the texture of the iris in people with dark eyes is poorly distinguishable in the visible range at registration, and vice versa, the texture of the iris in people with light eyes will be poorly distinguishable in the infrared range [6].…”
Section: B Scenariomentioning
confidence: 99%
“…The authors are not aware of any open or public competition for retina biometrics. For sclera-based biometrics, sclera segmentation (and recognition) competitions have been organised 2015-2018 7 (SSBC'15 [45], SSRBC'16 [46], SSERBC'17 [48], SSBC'18 [47]) based on the SSRBC Dataset (2 eyes of 82 individuals, RGB, 4 angles) for which segmentation ground truth is being prepared. However, this dataset is not public and only training data are made available to participants of these competitions.…”
Section: Eye-based Vascular Traitsmentioning
confidence: 99%
“…A template based matching was introduced using hamming distance for classification in [23], [24]. For recognition, a benchmarking competition was organized to record the recent advancements in recognition techniques where the winning team achieved 72.56% accuracy in eye recognition [25]. From various literature, it is observed that many challenges are being addressed by various researchers to improve the accuracy of the recognition system.…”
Section: Introductionmentioning
confidence: 99%